Effect Of Nitrogen Fertilization And Supplementation On The Nutritive Value And Utilization Of Setaria Sphacelata Var. Splendida In Dairy Bulls - Mamat, Mustapha (1988)

(untitled)
Three experiments were conducted at the Dairy Farm, Department of Animal Sciences, Universiti Pertanian Malaysia, Serdang, using four cross-bred dairy bulls, Jersey O X Local Indian Dairy O. The main objective of the study was to evaluate the effect s of nitrogen fertilization and supplementation with urea and leucaena on the nutritive value and utilization of Setaria sphacelata var. splendida in cattle. The indices measured included rumen degradability, in vivo digestibility, feed intake and the concentration of ammonia-N in the rumen liqour. In the balance studies, nitrogen intake and nitrogen balance were determined.The results of Experiment I showed that the yields of dry matter and nitrogen of the fertilized were higher than those of the unfertilized forages , but the response ( kg per kg nitrogen applied ) in both dry matter and nitrogen was decreasing with increasing nitrogen fertilization.